Klasifikasi Keluhan Tamu Mengenai Pelayanan Front Office di The Westin Resort Nusa Dua Bali Berdasarkan Ulasan pada Tripadvisor - Putu Diana Ayu Pratiwi; I Gusti Ayu Putu Wita Indrayani; I Made Sucipta Adnyana (JURNAL BISNIS HOSPITALITI, 2021)
The purpose of this study is to discover the reasons and effects of recurring complaints based on the classification of guest complaints about Front Office services at The Westin Resort Nusa Dua Bali, in order to identify alternative methods to reduce the number of guest complaints. The data was gathered through documentation on TripAdvisor and an interview with the Front Office Manager, and the data analysis technique applied was descriptive qualitative. The analysis's findings revealed the reasons and consequences of guest complaints about Front Office services, which were classified into two categories: service-related complaints and attitudinal issues. Furthermore, the front office service procedures have not achieved 100 percent compliance with the SOP during the guest cycle. In the case of attitudinal complaints and service-related complaints, the reason of the complaints was determined as a disparity in SOP. This research was effective in enhancing comprehension of the reasons and effects of guest complaints regarding Front Office services on Online Travel Agents. Based on the research that has been conducted, suggestions should be addressed to hotel management as an alternate option to reduce problems that have occurred by enrolling in training.